Corticospinal and intracortical responses from both motor cortices following unilateral concentric versus eccentric contractions. (17th January 2023) - van der Groen, Onno; Latella, Christopher; Nosaka, Kazunori; Edwards, Dylan; Teo, Wei‐Peng; Taylor, Janet L.
Abstract: Cross‐education is the phenomenon where training of one limb can cause neuromuscular adaptations in the opposite untrained limb. This effect has been reported to be greater after eccentric (ECC) than concentric (CON) strength training; however, the underpinning neurophysiological mechanisms remain unclear. Thus, we compared responses to transcranial magnetic stimulation (TMS) in both motor cortices following single sessions of unilateral ECC and CON exercise of the elbow flexors. Fourteen healthy adults performed three sets of 10 ECC and CON right elbow flexor contractions at 75% of respective maximum on separate days. Elbow flexor maximal voluntary isometric contraction (MVIC) torques were measured before and after exercise, and responses to single‐ and paired‐pulse TMS were recorded from the non‐exercised left and exercised right biceps brachii. Pre‐exercise and post‐exercise responses for ECC and CON were compared by repeated measures analyses of variance (ANOVAs). MVIC torque of the exercised arm decreased ( p < 0.01) after CON (−30 ± 14%) and ECC (−39 ± 13%) similarly. For the non‐exercised left biceps brachii, resting motor threshold (RMT) decreased after CON only (−4.2 ± 3.9% of maximum stimulator output [MSO], p < 0.01), and intracortical facilitation (ICF) decreased (−15.2 ± 20.0%, p = 0.038) after ECC only. For the exercised right biceps, RMT increased after ECC (8.6 ± 6.2% MSO, p = 0.014) but not after CON (6.4 ± 8.1% MSO, p = 0.066). Thus, unilateral ECC and CON elbow flexor exercise modulated excitability differently for the non‐exercised hemisphere. These findings suggest that responses after a single bout of exercise may not reflect longer term adaptations. Abstract : Cross‐education of muscle strength occurs after periods of unilateral resistance training and is thought to be underpinned by neural adaptations. The magnitude of cross‐education is generally greater when eccentric contractions are performed. This study investigated transcranial magnetic stimulation responses from both motor cortices before and after a single session of unilateral eccentric or concentric elbow flexor contractions to better understand the central mechanisms that may underpin longer term cross‐education effects. Unilateral eccentric and concentric elbow flexor exercise modulated excitability differently for the non‐exercised hemisphere. As the direction of this modulation was unexpected, the acute responses observed in this study may not reflect longer term cross‐education effects.